Adaptation of Multi-platform Broadcasting Management in the Disruption Era: A Case Study of Private Television in Indonesia - Anggi Arifudin Setiadi; Subhan Afifi; Basuki Agus Suparno (Department of Communications, Universitas Islam Indonesia, 2021)
The disruption era is characterized by massive, rapid and unpatterned changes, causing uncertainty, unclear direction and complex relationships between factors driving the change. This epoch is accelerated by the massive use of digital technology with several main characteristics, such as the increasing importance of artificial intelligence, the internet of things, virtual reality, and three-dimensional printing machines. Such rapid changes require private television managers to adapt broadcasting practices to capture opportunities and anticipate threats. Taking a case study of private television in Indonesia, this article explores how multiplatform broadcast media adjust to such rapid changes. Applying the value chain concept as a theoretical framework, this study investigates five essential aspects of the broadcast production chain: content creation, packaging, scheduling, distribution platform, and user interface. The research method was descriptive qualitative with in-depth interviews, observations, and documentation studies as the primary data collection methods. This study shows that the packaging aspect is a new strategy in multiplatform broadcasting management by determining the target audience of a packaged program. The user interface strategy using multiple platforms allows the interaction with the audience. The broadcasting work management system using Trello enables television workers to work anywhere without coming to the office. Flexibility and time efficiency are applied in broadcasting work management. At the same time, the target market of the millennial generation who rarely watches television but watches YouTube broadcasts is responded by designing programs and channels that are more suited to the millennial character. Keywords: Multiplatform broadcasting management, disruption era, broadcasting value chain, private television